Determination of Safety Stock and Reorder Point Using Spreadsheet Simulation for Inventory Control of Packaging Materials - Pamolango, Marchello; Dewantoro, Albertus Daru (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Effective inventory control is essential in make-to-order (MTO) flexible packaging operations, where packing materials often exhibit irregular and highly variable usage patterns. This study proposes an integrated inventory control model that combines probabilistic Safety Stock (SS) and Reorder Point (ROP) calculations with a spreadsheet-based Traffic Light System (TLS) as a practical, low-cost monitoring tool. Using historical consumption and supplier lead-time data, the analysis determines demand variability and applies a 90% service level (Z = 1.28) to calculate buffer stock requirements. Results show that high usage variability substantially increases SS and ROP values. For the key item examined, SS is calculated at 265 units and ROP at 1,380 units, highlighting the importance of statistical methods compared to manual estimation. The TLS simulation applied across all materials improves early detection of low-stock risks and enhances PPIC responsiveness. Sensitivity testing indicates that raising the service level to 95% increases SS by about 28%, demonstrating the trade-off between reliability and inventory costs. This study contributes by integrating SS–ROP computation, usage classification, and real-time visual monitoring into a unified operational framework. The model strengthens data-driven decision-making and reduces stockout risk in flexible packaging manufacturing.